2018
DOI: 10.1590/1980-5373-mr-2018-0167
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Photocatalytic Properties of Flower-like Mn-doped Ceria

Abstract: Mn-doped CeO 2 flower-like microstructures have been synthesized by a facile one-step compositehydroxide-mediated method. The structure, morphology, optical and the surface properties of Mn doped CeO 2 have been investigated by X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), UV-Vis absorption spectroscopy and X-ray photoelectron spectroscopy (XPS). The XRD results confirmed the successful incorporation of Mn into the CeO 2 lattice through the formation of face-centered cubic solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…3 presents XRD patterns of the prepared samples before (a) and after reaction (b). Mn-, Cu-, and Zn-doped CeO 2 samples had peaks in approximately the same position corresponding to (111), (200), (220), (311), (222), and (400) planes according to the XRD patterns, being in agreement with Joint Committee on Powder Diffraction Standards (JCPDS) cards [28][29][30] report by Takalkar [31] for the crystallite size of CeCu, CeZn, and CeMn in the order of CeCu > CeMn > CeZn. XRD patters of samples after ESR (Fig.…”
Section: Catalyst Characterizationsupporting
confidence: 79%
See 1 more Smart Citation
“…3 presents XRD patterns of the prepared samples before (a) and after reaction (b). Mn-, Cu-, and Zn-doped CeO 2 samples had peaks in approximately the same position corresponding to (111), (200), (220), (311), (222), and (400) planes according to the XRD patterns, being in agreement with Joint Committee on Powder Diffraction Standards (JCPDS) cards [28][29][30] report by Takalkar [31] for the crystallite size of CeCu, CeZn, and CeMn in the order of CeCu > CeMn > CeZn. XRD patters of samples after ESR (Fig.…”
Section: Catalyst Characterizationsupporting
confidence: 79%
“…3 presents XRD patterns of the prepared samples before (a) and after reaction (b). Mn-, Cu-, and Zn-doped CeO 2 samples had peaks in approximately the same position corresponding to (111), ( 200), ( 220), (311), (222), and (400) planes according to the XRD patterns, being in agreement with Joint Committee on Powder Diffraction Standards (JCPDS) cards [28][29][30]. Differences in intensity or a little position shift com-pared to CeO 2 indicated the formation of Mn-, Cu-, and Zn-doped CeO 2 and peaks related to CuO, ZnO, and Mn x O y could be justified by more dopant from the CeO 2 lattice, so remaining on the surface was detected.…”
Section: Catalyst Characterizationsupporting
confidence: 79%
“…Notwithstanding this, some authors have reported that CeO 2 presents a disadvantage related to the rapid recombination of the charge carriers (e − − h + ) formed in the process, which limit its applications in photocatalytic processes. 29,30 In order to reverse this disadvantage, modifications of the semiconductor by addition of transition metals 25,31 and metallic oxides 32 have successfully enhanced the physicochemical properties and increase the photoactivity of the material. This modification with transition metals by doping might induce crystalline defects and favor charge transference towards adsorbed species increasing photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…For direct band gap semiconductors, the exponent n equals 1/2, whereas for indirect band-gap semiconductors, it equals 2. Given that Ce-La-based composites exhibit indirect band-gap characteristics [31], an exponent of n = 2 was employed in our analysis. Based on these calculations, the band gaps of Ce-La, Ce-La-Pr, and Ce-La-Mn are 2.30 eV, 2.01 eV, and 1.91 eV, respectively.…”
Section: Crystal Structure Morphology Of Compositesmentioning
confidence: 99%